PENYAKIT CAMPAK (MORBILI) PADA ANAK DI BAGIAN ILMU KESEHATAN ANAK RSU PROF. Dr.R.D.KANDOU MANADO - ., Irmawati (Jurnal Entropi, 2009)
Measles is a serious problem in many developing countries included Indonesia. This research aims to find out how the general description of Measles, the death rate and the complications to sufferers. This research used Retrospective and takes the data from medical record of Pediatrics in General Hospital of Dr. R.D. Kandou Manado on January, 2000 until December, 2003. The research result is Measles happened in each 2 until 4 year and attacked most to 5-9 years old children. In addition, there are no gender differences. Failure to immunization was caused by primer and secondary. The death is found in measles sufferer who are not immunized and malnutrition. Bronchopneumonia is the most complication to the sufferers and the most treatment is symptomatic.